2015
DOI: 10.1002/bip.22638
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of polymers: An important system to overcome the cell barriers in gene transfection

Abstract: Delivery of the macromolecules including DNA, miRNA, and antisense oligonucleotides is typically mediated by carriers due to the large size and negative charge. Different physical (e.g., gene gun or electroporation), and chemical (e.g., cationic polymer or lipid) vectors have been already used to improve the efficiency of gene transfer. Polymer-based DNA delivery systems have attracted special interest, in particular via intravenous injection with many intra- and extracellular barriers. The recent progress has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 140 publications
0
29
0
Order By: Relevance
“…PEG has been used to coat PLA nanoparticles, and it usually aggrandizes the solubility of nanoparticles, decreasing their aggregation and interaction with proteins in physiological fluids. This produces spatial stability on the surface of the gene carrier to enhance transfer efficiency [45]. Compared to the bulk materials and microparticles, nanoparticles exhibit different mechanical properties.…”
Section: Physiochemical Properties Of Polymer-based Nanoparticlesmentioning
confidence: 99%
“…PEG has been used to coat PLA nanoparticles, and it usually aggrandizes the solubility of nanoparticles, decreasing their aggregation and interaction with proteins in physiological fluids. This produces spatial stability on the surface of the gene carrier to enhance transfer efficiency [45]. Compared to the bulk materials and microparticles, nanoparticles exhibit different mechanical properties.…”
Section: Physiochemical Properties Of Polymer-based Nanoparticlesmentioning
confidence: 99%
“…The structural diversity in polymers for gene delivery contains cationic residues, endosomal escape units, and degradable fragments. [29,30] Some examples of polymers such as Chitosan, Gelatin, Polyethylene imine (PEI), Poly lactic-co-glycolic acid (PLGA) and poly lactic acid (PLA), Dendrimers were described as following.…”
Section: Polymersmentioning
confidence: 99%
“…Past research has shown that to achieve successful transfection, nonviral delivery systems, such as those delivering siRNA, need to overcome several cellular barriers, including being internalized by cells, escaping from endolysosomes, and dissociating the cargo from the complex for delivery into the cytoplasm. 3 Endocytosis has been established as the main mechanism for the uptake of nonviral vectors into the cells. 4 Endocytosis can be classified into five categories: phagocytosis, clathrin-dependent endocytosis (CDE), caveolae-mediated endocytosis (Cav-ME), non-clathrin-and non-caveolae dependent endocytosis, and macropinocytosis.…”
Section: Introductionmentioning
confidence: 99%